PERCEIVED STRESS OF HIGH SCHOOL STUDENTS IN SOUTH KOREA: A DATA ANALYSIS - Kilicheva Karomat; Klicheva Gavkhar (Galaxy International Interdisciplinary Research Journal, 2021)
Students experience extreme levels of stress in intense academic environment in South Korea. Such school-related stress levels reach its peak in the final year of high school, as students prepare for college entrance exam. To perform better on the college entrance exam and gain admission to Korea’s most prestigious universities, Korean students devote a significant portion of their early lives to studying. Stress is often linked to schooling among adolescents. Academic stress is mainly associated with school performance, including exams and homework. This paper, thus will analyze the latest trends for high school stress among students in Korea by gender and average monthly income compared to other countries and suggest main reasons with implications.